Enriching Students’ Vocabulary through Kahoot - Amuati, Siti Asriani; Mestari, Sri Agriyanti; Badu, Helena (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this research is to determine whether the use of the game Kahoot can enrich students' English vocabulary. The method used in this research is a quantitative pre-experimental design. The sample in this study consisted of 19 students from Class VII B of SMP N 7 Gorontalo. The researcher collected pre-test and post-test scores for data analysis, then calculated the mean scores and percentage scores. The mean score of the students in the pre-test was 57.3, while the mean score of the students in the post-test was 72.2. Therefore, it can be concluded that the game Kahoot can improve and further enrich students' English vocabulary. The results of this research show that the working hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.